Stress Levels and Blood Sugar Control in Patients with Type 2 Diabetes Mellitus - Kalyana Falen Danaswara; Fahrun Nur Rosyid (GLOBAL HEALTH SCIENCE GROUP, 2026)
The prevalence of type 2 diabetes mellitus (T2DM), a chronic condition, is on the rise around the world. Glycemic regulation, which includes unexpected blood glucose levels, is impacted by both biological and psychological influences, including stress. Specifically, studies examining the impact of stress on unforeseen glucose regulation have been under-researched in Indonesia. This research aims to fill a gap in our understanding of how stress influences individuals' ability to deliberately regulate their blood sugar levels. Those taking part in the study were monitored using a cross-sectional method. Two hundred patients with type 2 diabetes mellitus were selected from the patient registry of the Baki Community Health Center based on a list of predefined inclusion and exclusion criteria. We measured the amount of stress and then categorized it as low, medium, or high using the Perceived Stress Scale (PSS). Stress levels were measured using the Indonesian version of the Perceived Stress Scale-10 (PSS-10), which had been previously validated and demonstrated good reliability (Cronbach’s Alpha α = 0.84). During data collection, a single RBG test was performed to evaluate the impact of random modulation on blood glucose levels. In both the univariate and bivariate data analyses, Pearson's Chi-Square test was employed with a significance level of p < 0.05 to determine if the variables were related. We utilized Cramer's V to determine the reliability of the association. This study was authorized by the Health Research Ethics Committee of the Faculty of Medicine at Muhammadiyah University Surakarta. The study comprised 200 participants, the average age of whom was 41.82 ± 6.50 years. Women comprised 67.5% of that group. On average, 244.07 ± 84.46 mg/dL was recorded by 60% of those whose levels were uncontrolled and 51.5% of those who indicated moderate stress. The results of the bivariate analysis showed a significant relationship (χ² = 81.919; p < 0.001) between the levels of stress and the random control of blood glucose. Their bond was strong. People with type 2 diabetes mellitus find it more difficult to regulate their blood glucose levels when they are under a lot of stress. A substantial and statistically significant relationship exists here. The results show that mental stress needs to be taken into account while managing blood sugar levels thoroughly.